Pengaruh Digitalisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Vania Rakhmadhani (Fakultas Ekonomi Universitas Garut, 2026)
Tax digitalization is a strategic effort undertaken by the Directorate General of Taxes (DGT) to enhance efficiency, transparency, and taxpayer compliance. This study aims to analyze the impact of tax digitalization on the compliance of individual taxpayers in Indonesia. Using a quantitative descriptive Method, data were collected through surveys of individual taxpayers who have utilized digital systems such as e-filing, e-billing, and e-payment. Data analysis was conducted using regression methods to measure the significant influence of digitalization on tax compliance. The results indicate that tax digitalization has a positive impact on taxpayer compliance. Challenges such as low digital literacy and resistance to change remain obstacles in the implementation of this system. Tax digitalization is proven to enhance taxpayer compliance, driven by technological understanding, perceived ease of use, and perceived benefits. The Directorate General of Taxes (DGT) needs to strengthen digital literacy programs and change management strategies to ensure a more inclusive and effective system implementation, capable of optimizing state revenue.